Challenges in understanding inequities in help-seeking for possible cancer symptoms - Katriina L. Whitaker; Tetyana Perchyk; Robert S. Kerrison; Agnieszka Lemanska (BMC, 2024)
Abstract Tackling inequities in cancer outcomes is a global health priority. One avenue for improving early diagnosis of cancer is to ensure people know when and how to seek help for cancer symptoms and that this knowledge (and behaviour) is equitably distributed across the population. In this perspective piece we highlight the challenges in understanding sociodemographic differences in help-seeking behaviour (for example, how help-seeking is defined / conceptualised and subsequently assessed), as well as challenges with using existing datasets that are now more readily accessible than ever. Addressing these will strengthen methodological approaches to understand inequities in help-seeking and ways to tackle them.